Oxidation of difluorocarbene and subsequent trifluoromethoxylation - Jiao Yu (Nature Portfolio, 2019)
Difluorocarbene is a versatile and efficient intermediate for fluorine incorporation. Here, the authors show that difluorocarbene can be oxidized to carbonyl fluoride and this process is confirmed in 18O-trifluoromethoxylation reactions, by observation of AgOCF3 species and theory.